KAJIAN IDENTIFIKASI FAKTOR UNTUK PENGEMBANGAN USAHA WARUNG TEGAL (WARTEG) MASUK MALL (STUDI KASUS DI JABODETABEK) - Novianti, Mirsa Diah; Susanto, Tri; Hatta, Holilla; Johannes, Rene (Journal of Entrepreneurship, Management and Industry (JEMI), 2018)
This study aims to analyze business development strategies from traditional food stalls (case studies: tegal stalls in Jabodetabek). The research method uses descriptive qualitative method with data collection techniques through focus group discussion. The results of this study are the need for training to improve market access, legality aspects and competitive advantage